NEEDS ANALYSIS OF ESP FOR TOURISM STUDY PROGRAM AT SMKN 7 (SENIOR VOCATIONAL SCHOOL) KOTA BENGKULU - Rezky Oktarin; syahrial .; Alamsyah Harahap (Journal of English Education and Teaching, 2019)
The design of this research is quantitative-qualitative descriptive research. The purpose of this research are first to analyze the English learning needs of students in Tourism Study Program and second to analyze the suitability of existing English textbook used. The subjects of this research are students of SMKN 7 Bengkulu 12th grade, English teachers in SMKN 7 Bengkulu, graduates of Tourism Study Program, and the English language users in the field of Tourism. In this study, researcher used the needs analysis to find what are the need, lacks, and want of students in learning English. The instruments that used in this study are questionnaires, interview, and existing English textbooks used in English language learning. The result of the research indicate that the needs of the Tourism Study Program student grade XII of SMKN 7 Kota Bengkulu are materials and activities that support their activities to work in the tourism field and the existing English textbook used by Tourism Study Program student grade XII of SMKN 7 Kota Bengkulu that is English textbook from Kementerian Pendidikan dan Kebudayaan Indonesia (2015) do not cover the students’ need.